The Fatimids and Egypt - Brett, Michael, 1934- (Variorum collected studies series, 2019)
This Variorum volume is a collection of articles dealing with Egypt under the Fatimids, originally published in diverse journals and books between 1984 and 2013. The Fatimids came to power in North Africa in 910 CE, and ruled in Egypt from 969 to 1171 CE. As Imams and Caliphs, they claimed authority for the faith and the government of the Muslim world. In Egypt and Syria, they both reigned and ruled over the state. In North Africa and Sicily, the Hijaz and latterly the Yemen, they reigned but did not rule. In the rest of the Muslim world, they pursued their aim for recognition, notably through their missionaries active in Iraq and Iran